A New Approach of Sperm Motility Subpopulation Structure in Donkey and Horse - Gacem, Sabrina; Valverde, Anthony; Catalán, Jaime; Yánez Ortiz, Iván; Soler, Carles; Miró, Jordi (Frontiers in Veterinary Science, 2021)
This study aimed to characterize the sperm kinematic values with high frames per second, in order to define the subpopulation structure of horse and donkey and compare them. A total of 51 fresh semen ejaculates (26 Spanish and 16 Arabian horse breeds, and 12 donkeys) were collected, and subsequently analyzed for kinematic parameters by using the computer-assisted semen analysis (CASA‐Mot) ISAS®v1.2 system and using a Spermtrack® 10µm depth counting chamber. Sequences were recorded at 250 frames per second and eight kinematic parameters were automatically evaluated. All kinematic parameters showed significant differences between donkey and horse, and between horse breeds. All ejaculates evaluated showed excellent semen motility characteristics; with significantly higher values for all kinematic parameters for donkeys compared to horses except for BCF. Donkey sperm was faster and linear than the horse. Regarding horse breeds differences, the Spanish horse had higher VAP, VCL and BCF compared to the Arabian horse. Spanish horse sperm was rapid but Arab horse was more linear. The principal component analysis showed three sperm subpopulations in the ejaculate of donkeys and horses with a significantly different motility characteristic between them. The dominant subpopulation for both donkey and horse was for rapid, straight and linear with a high beat sperm (38.2% and 41.7% respectively) while the lowest subpopulation was for the slowest and non-linear sperms. This, plus slight differences in the distribution of these subpopulations between Arabian and Spanish horse were found. In conclusion, higher frames permitted to have a new interpretation of motile subpopulations with specie and breed differences. More so, future works on donkey and horse breeds spermatozoa should take into account differences between breeds which may interfere and alter the real analysis performed.